Electrical Measurements and Analyses with Data Acquisition Devices (DAS) of Heating and Cooling Capacities of the Intercity Coaches - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2009)
Predominantly coaches are preferred for intercity passenger transportation in our country. Vehicles are supposed to meet the passengers' expectations in terms of safety, comfort and health during journey. Some features such as an internal environment that has an adequate and balanced temperature level is one of the essentials of the features affecting passenger comfort directly. To provide these, various coach manufacturer firms are continuing to make many trials and test studies at design stage. For that purpose, the vehicle-heating and cooling capacities of the intercity coaches were analyzed and examined in the scope of this study, by means of the thermometers and data acquisition systems (DAS). The thermal measurements related the subject were made on the intercity coaches at the Development & Test Center of a intercity coaches producer firm. The measurement results obtained from the experimental studies were examined and in consequence of the assessment of these data, implementation of the optimum resolutions was recommended in terms of passenger health and comfort.
Keywords: Measurement; analyses of heating and cooling capacities